User-Centered Design pada Pengembangan Interface Web Penyedia Jasa Pembuatan Undangan Pernikahan (Fairytale) - Latief Naufal Andryanto (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This study aims to develop a web interface for a digital wedding invitation service provider (Fairytale) using the User-Centered Design (UCD) approach. The research method follows the UCD approach, consisting of four main stages: (1) understanding the context of use, (2) identifying user needs, (3) designing solutions, and (4) design evaluation. Data collection involved 36 respondents through questionnaires, interviews, and usability testing. The findings highlight three key functional requirements: template customization (94.4%), guest list management (88.9%), and digital RSVP (86.1%). The implementation of UCD resulted in significant improvements in usability metrics: task success rate increased from 65% to 91.7%, error rate decreased from 35% to 8.3%, and user satisfaction rose from 3.2 to 4.3 (on a 1-5 scale). Mobile-first optimization became a central focus, given that 72.2% of users prefer accessing the platform through mobile devices. This research contributes to the development of the UCD model for digital platforms in Indonesia and provides practical guidelines for user-centered interface development. The study's limitations include a small sample size and a geographically focused scope, suggesting opportunities for future research with a larger scale..